Analysis of mismatch power loss and degradation in aged PV modules and arrays: Insights from an indoor experimental investigation - Islam, Md. Imamul; Al Mansur, Ahmed; Mohd Shawal, Jadin; Maruf, Md Hasan; Shihavuddin, Asm S.M. (Springer, 2024)
Their performance suffers once PV modules are subjected to extreme internal and external stress over an extended period. The PV system arrays met such variables that resulted in mismatched power losses in the array while producing energy at a large scale. This research aims to comprehend how irradiance and ageing contribute to mismatch loss in PV arrays. This study considers three array configurations—series, parallel, and series–parallel—while evaluating the output performance degradation of PV modules at two distinct irradiances, 1000 and 800 W/m2. The experiment results show that the deterioration of module power is caused by both irradiance and age. At 800 W/m2, the MML% for the series, parallel, and series–parallel topologies are 44.73%, 38.01%, and 42.2%, respectively. At 1000 W/m2, the MML% for the same configurations falls to 30.9, 22.51, and 27.9%. Furthermore, the parallel setup displays a lower MML for both irradiances than the other configurations. Moreover, in the analysis of PV module degradation, Mono 1 was found to be the most degraded panel (0.344) among the four panels that were exposed outside for 10 years. These results emphasize the need to address irradiance and ageing in solar energy systems by stressing their negative impacts on power degradation and MML in PV modules and arrays.